National Pedagogical Transformation: Problems and Solutions - A. Hamdamov (European Journal of Life Safety and Stability (2660-9630), 2023)
The article describes the content of national pedagogy in Uzbekistan and its innovations, researches, their results, and related problems and their solutions theoretically and practically.